Efektivitas model pembelajaran kooperatif tipe two stay two stray terhadap hasil belajar IPA ditinjau dari motivasi belajar siswa - Yuni Rachmawati; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2018)
This research is descriptive to know the tendency of science learning result and student learning motivation through Cooperative Learning Model of TSTS Type and Direct Learning Model. Comparatively to know the difference of science learning outcomes of the seventh grade students of SMP Negeri 11 Yogyakarta in the academic year 2016/2017 between the TSTS type cooperative model and the direct model in terms of student learning motivation. Type of Quasi Experimental research. Analyze data with anacova. Anacova test results obtained Fcount = 32.638 with p = 0,000, because p â‰¤ 0.01 then concluded there is a very significant difference. Descriptively the tendency of science learning outcomes and student learning motivation with cooperative model type TSTS higher than direct model. means cooperative learning model TSTS type more effective in improving science learning outcomes compared with direct learning model in terms of student's learning motivation.